Neuroprotective Biomarkers and Cognitive Function in a Long-Term Prospective Population-based Study of Aging US Adults. (January 2020) - Paulsen, Adam J.; Schubert, Carla R.; Pinto, Alex; Carlsson, Cynthia M.; Chappell, Richard J.; Fischer, Mary E.; Klein, Barbara E.K.; Klein, Ronald; Tsai, Michael Y.; Cruickshanks, Karen J.
Abstract : Background: Relationships between brain-derived neurotrophic factor (BDNF), insulin-like growth factor (IGF-1), aldosterone, and cognition in aging were evaluated in the population-based Epidemiology of Hearing Loss Study (1993 to present). Methods: Beginning in 1998 to 2000, cognitive impairment was assessed by report of physician diagnoses and the Mini-Mental State Examination. In 2009 to 2010 and 2013 to 2016, information was collected on diagnosis of mild cognitive impairment/dementia. Decline in cognitive function was assessed by principal component analysis from additional tests administered during 2009 to 2010 and 2013 to 2016. BDNF, IGF-1, and aldosterone were measured in serum collected in 1998 to 2000. Results: There were 1970 participants (mean age=66.9 y; 59.1% female) without cognitive impairment at baseline. Among women, low BDNF was associated with 16-year incident cognitive impairment [hazard ratio=1.76; 95% confidence interval (CI)=1.04, 2.98]. Among men, increasing IGF-1 was associated with decreased risk [per SD: relative risk (RR)=0.57; 95% CI=0.35, 0.92], whereas increasing aldosterone levels were associated with increased risk (per SD: RR=1.28; 95% CI=1.01, 1.62) for 5-year incident mild cognitive impairment/dementia. Overall, low BDNF was associated with increased risk (RR=1.52; 95% CI=1.02, 2.26) for 5-year cognitive decline. Conclusion: Low levels of serum BDNF and IGF-1 were associated with poorer cognition during aging. There may be differential biomarker effects by sex.